2018
DOI: 10.1002/lipd.12099
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Fatty Acids Increase the Expression of Hepassocin through a Signal Transducer and Activator of Transcription 3‐Dependent Pathway in HepG2 Cells

Abstract: Hepassocin (HPS) is a hepatokine that regulates hepatocyte proliferation. It is known that HPS plays an important role in the development of nonalcoholic fatty liver diseases (NAFLD). Fatty acids, such as oleic acid (OLA), exhibit the ability to activate the signal transducer and activator of transcription‐3 (STAT3), and the binding site of STAT3 is found in the promoter region of HPS. However, the regulation of HPS by fatty acids is still obscure. To clarify the regulation of HPS, we detected the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…In addition, it is known that interleukin-6 (IL-6) increases hepassocin expression [27], indicating that elevated hepassocin might also be involved in obesity-induced IR. Furthermore, Cheng et al found that activation of signal transducer and activator of transcription-3 by IL-6 were mediated by hepassocin expression [28]. In the current study, it was revealed that the high hepassocin group had a higher waist-to-hip ratio compared with the low hepassocin group, and with increasing hepassocin tertiles, there were significant increases in hs-CRP concentrations as well as neutrophil and monocyte counts.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, it is known that interleukin-6 (IL-6) increases hepassocin expression [27], indicating that elevated hepassocin might also be involved in obesity-induced IR. Furthermore, Cheng et al found that activation of signal transducer and activator of transcription-3 by IL-6 were mediated by hepassocin expression [28]. In the current study, it was revealed that the high hepassocin group had a higher waist-to-hip ratio compared with the low hepassocin group, and with increasing hepassocin tertiles, there were significant increases in hs-CRP concentrations as well as neutrophil and monocyte counts.…”
Section: Discussionsupporting
confidence: 51%
“…Mechanistically, there are potential binding sites of STAT3 in the FGL1 gene promoter, and unsaturated fatty acid activates STAT3 to increase FGL1 expression. The blockade of STAT3 dose-dependently inhibited unsaturated fatty acid induced FGL1 expression, which accounts for the increased level of FGL1 under proinflammatory conditions [24]. In addition, FGL1 regulates NAFLD through an ERK1/2-dependent pathway [22].…”
Section: Fgl1 In Nonalcoholic Fatty Liver Diseasementioning
confidence: 98%
“…HPS expression in BAT and liver was increased following partial hepatectomy in mice [110] and by IL-6 in vitro [107], suggesting a cross talk between the injured liver and adipose tissue [110]. Oleic acid increased HPS expression via activation of Signal transducer and activator of transcription 3 (STAT3) signaling and induced IR in HepG2 cells [111], while palmitic acid induction of HPS occurred through p38-modulated CCAAT/enhancer binding protein binding to the HPS promoter in mice [112]. HPS administration protected against liver injury and improved the survival of lethal hepatitis in rats [113].…”
Section: Hepatokinesmentioning
confidence: 99%